Analisis Kesiapan Penerapan Rekam Medis Elektronik Di Klinik AMC ‘Aisyiyah - Muhlizardy Muhlizardy; Winda Azmi Meisari; Ummu Muti’ah; Meylia Isna (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Electronic Medical Records (EMR) is one of the health IT applications that is becoming a trend around the world. EMRs are considered to improve the overall quality of care and have an impact on patient safety. EMRs can also help reduce costs, improve accessibility, and improve the quality of hospital services. Therefore, the preparedness analysis of the implementation of EMR with the DOQ-IT approach (Doctor's Office Quality-Information Technology) is the goal of this research. This research uses a type of quantitative descriptive research with a cross sectional approach. The samples were taken from all the officers who were in direct contact with the medical records at AMC Aisyiyah Clinic. Sampling technique using a total sampling of eight officers. Primary data collection is done with a questionnaire. The method of analysis used is descriptive analysis of frequencies, percentages, graphs and tables. From the results of analysis using the DOQ-IT method obtained a total score of 104.75 belongs to category III which shows that human resources, organizational work culture, governance and leadership, IT infrastructure AMC Aisyiyah Clinic is ready to take advantage of EMR as well as overcome the potential challenges for successful adoption of the EMR.